Cyclodextrins as Multi-Functional Ingredients in Dentistry - Susana Santos Braga (MDPI AG, 2023)
Cyclodextrins are present in a variety of oral hygiene compositions. The present work describes the role of cyclodextrins in several toothpastes and mouthwashes that are already available in the market, as well as their prospective use in other applications as investigated in studies in the literature. Moreover, cyclodextrins are under study for the development of materials used in various techniques of dental repair, such as fillings, cements and binders therein. Their role in each of the innovative materials is presented. Finally, the prospect of the use of cyclodextrin-based delivery systems for the oral cavity is introduced, with a focus on new cyclodextrin molecules with dual action as bone-targeting agents and osteogenic drugs, and on new cross-linked cyclodextrin particles with a high drug loading and sustained drug delivery profile for the treatment of diseases that require prolonged action, such as periodontitis. In conclusion, cyclodextrins are herein demonstrated to act as versatile and multi-action ingredients with a broad range of applications in dentistry.